Antiretroviral therapy and liver disorders in the OPERA® cohort. (December 2020) - Wohlfeiler, Michael; Mounzer, Karam; Brunet, Laurence; Fusco, Jennifer; Vannappagari, Vani; Curtis, Lloyd; Payvandi, Nassrin; Aboud, Michael; Hsu, Ricky; Lackey, Philip; Fusco, Gregory
Introduction: A comprehensive assessment of liver disorders was conducted among people living with HIV (PLWH) on a new antiretroviral regimen based on common core agents. Methods: Treatment-naïve and experienced PLWH first initiating dolutegravir (DTG), elvitegravir (EVG), raltegravir (RAL), or darunavir (DRV) in the OPERA ® cohort were included if they had ⩾1 liver chemistry test performed both within 12 months before regimen start and over follow-up. Liver disorders were defined as a diagnosis of drug-induced liver injury (DILI) or moderate/severe liver chemistry elevations (LCE). History of liver disorders experienced within 12 months of initiation was summarized. Liver disorders occurring during follow-up were described as prevalent (all disorders) or incident (disorders occurring among PLWH without a history of liver disorders or advanced liver fibrosis). Results: Out of 16, 024 PLWH, 38% initiated DTG, 43% EVG, 5% RAL, and 14% DRV. EVG users were younger and had a lower likelihood of comorbidities or lipid-lowering agent use than DTG users. EVG users were significantly less likely to have a history of moderate/severe LCE or to have prevalent moderate LCE. RAL users were older and had a higher likelihood of comorbidities or lipid-lowering agent use than DTG users. RAL users were significantly more likely to have a history of advanced liver fibrosis and prevalent moderate/severe LCE during follow-up. DRV users were older and had a lower likelihood of lipid-lowering agent use than DTG users. There was no difference in history of LCE, nor in prevalent or incident LCE between DRV and DTG users. No DILI diagnoses were recorded. Discontinuation following a liver disorder was rare (<1%) across all groups. Conclusion: While PLWH with comorbidities may have been channeled away from EVG and toward DTG and RAL, the incidence of moderate/severe LCE did not differ between DTG and EVG, RAL, and DRV. Plain language summary: Liver disorders and HIV treatment A comprehensive assessment of liver disorders was conducted using data from the OPERA ® cohort, which provides anonymous patient-level clinical data from electronic health records. People living with HIV (PLWH) who were starting a new HIV treatment regimen that included one of four common HIV drugs were included in this study. Liver disorders included drug-induced liver injury (DILI) and moderate or severe liver chemistry elevations. History of a disorder was defined as liver disorders that occurred before starting the new treatment. Prevalent disorders were those that occurred after starting the new treatment in the whole population. Incident disorders were those that occurred after starting the new treatment, but only among PLWH without any history of liver disorders. Out of 16, 024 PLWH, 38% initiated dolutegravir (DTG), 43% elvitegravir (EVG), 5% raltegravir (RAL), and 14% darunavir (DRV). EVG users were younger and less likely to have other diseases or use cholesterol lowering drugs compared to DTG users. They were also less likely to have a history of moderate/severe liver chemistry elevations or to have prevalent moderate liver chemistry elevations. RAL users were older and more likely to have other diseases or use cholesterol lowering drugs compared to DTG users. They were also more likely to have prevalent moderate/severe liver chemistry elevations than DTG users. DRV users were older and less likely to use cholesterol lowering agents compared to DTG users. There was no difference in history of liver chemistry elevations, or in prevalent, or incident liver chemistry elevations between DRV and DTG users. There were no DILI diagnoses and discontinuation of treatment following liver disorders was rare across all groups. Overall, the incidence of liver disorders after starting a new HIV treatment regimen did not differ between four common antiretroviral drugs.